Addressing Spirituality Within the Care of Patients at the End of Life: Perspectives of Patients With Advanced Cancer, Oncologists, and Oncology Nurses - Phelps, Andrea C. (J Clin Oncol, 2012)
PURPOSE: Attention to patients' religious and spiritual needs is included in national guidelines for quality end-of-life care, but little data exist to guide spiritual care. PATIENTS AND METHODS: The Religion and Spirituality in Cancer Care Study is a multi-institution, quantitative-qualitative study of 75 patients with advanced cancer and 339 cancer physicians and nurses. Patients underwent semistructured interviews, and care providers completed a Web-based survey exploring their perspectives on the routine provision of spiritual care by physicians and nurses. Theme extraction was performed following triangulated procedures of interdisciplinary analysis. Multivariable ordinal logistic regression models assessed relationships between participants' characteristics and attitudes toward spiritual care. RESULTS: The majority of patients (77.9%), physicians (71.6%), and nurses (85.1%) believed that routine spiritual care would have a positive impact on patients. Only 25% of patients had previously received spiritual care. Among patients, prior spiritual care (adjusted odds ratio [AOR], 14.65; 95% CI, 1.51 to 142.23), increasing education (AOR, 1.26; 95% CI, 1.06 to 1.49), and religious coping (AOR, 4.79; 95% CI, 1.40 to 16.42) were associated with favorable perceptions of spiritual care. Physicians held more negative perceptions of spiritual care than patients (P < .001) and nurses (P = .008). Qualitative analysis identified benefits of spiritual care, including supporting patients' emotional well-being and strengthening patient-provider relationships. Objections to spiritual care frequently related to professional role conflicts. Participants described ideal spiritual care to be individualized, voluntary, inclusive of chaplains/clergy, and based on assessing and supporting patient spirituality. CONCLUSION: Most patients with advanced cancer, oncologists, and oncology nurses value spiritual care. Themes described provide an empirical basis for engaging spiritual issues within clinical care.